Prevalence of breastfeeding in a baby-friendly pediatric practice in Trieste, Italy: follow up to 36 months of age - Mariarosa Milinco; Adriano Cattaneo; Anna Macaluso; Paola Materassi; Nicola Di Toro; Luca Ronfani (BMC, 2021)
Abstract Background A breastfeeding-friendly physician's office that applies the 13 recommendations of the Academy of Breastfeeding Medicine can help increase the exclusivity and duration of breastfeeding. Having already published the results up to five months of age of this intervention in our pediatric practice, we now report on the follow up to 36 months. Methods A cohort of 252 newborn infants was enrolled with our pediatric office in Trieste, Italy, between 1 January 2016 and 31 December 2016. The office implemented baby-friendly pediatric practices and a biological nurturing approach to the support of breastfeeding. In addition to the services offered by two pediatricians, support was provided by a peer counselor. Data on breastfeeding were collected at periodic healthy child visits up to 36 months of age. The outcome of interest for this follow up was the rate of any breastfeeding, defined as the percentage of infants and children who had received breastmilk in the previous 24 h. Results The rates of any breastfeeding at discharge and at 1, 3 and 5 months (n = 252) were 95.2, 95.8, 89.3 and 86.5%, respectively. At 8, 12, 18, 24 and 36 months of age, the rates of breastfeeding were 70.6% (163/231), 59% (135/229), 35% (78/224), 24.6% (55/224) and 7.2% (16/224), respectively. Conclusions The rates of any breastfeeding recorded in our pediatric practice up to age 36 months, are much higher than those reported elsewhere in high income countries and are likely to be associated with our baby-friendly and biological nurturing approach.